Sequence variation in the cytochrome oxidase subunit I and II genes of two commonly found blow fly species, Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) in Malaysia - Tan, S.H.; Aris, E.M.; Surin, J.; Omar, B.; Kurahashi, H.; Mohamed, Z. (2009)
The mitochondiral DNA region encompassing the cytochrome oxidase subunit I (COI) and cytochrome oxidase subunit II (COII) genes of two Malaysian blow fly species, Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) were studied. This region, which spans 2303bp and includes the COI, tRNA leucine and partial COR was sequenced from adult fly and larval specimens, and compared. Intraspecific variations were observed at 0.26 for Ch. megacephala and 0.17 for Ch. rufifacies, while sequence divergence between the two species was recorded at a minimum of 141 out of 2303 sites (6.12). Results obtained in this study are comparable to published data, and thus support the use of DNA sequence to facilitate and complement morphology-based species identification.